18F-FDG PET as a predictor of pulmonary function in sarcoidosis - Keijsers, R.G.; Verzijlbergen, F.J.; van den Bosch, et al., J.M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Fluor-18 fluorodeoxyglucose (18F-FDG) PET is able to demonstrate sarcoidosis activity. Ongoing pulmonary sarcoidosis activity can be reflected by a decline in pulmonary function tests (PFT).To assess whether diffuse metabolic activity of the lung parenchyma imaged by 18F-FDG PET predicts future pulmonary deterioration, 18F-FDG PET was compared with PFT. Methods: In this retrospective cohort study, 43 newly diagnosed, sarcoidosis patients were analyzed. Based on 18F-FDG PET, patients were diagnosed with diffuse parenchymal disease activity, without or with immunosuppressive treatment, started after 18F-FDG PET was performed. As a control, sarcoidosis patients with mediastinal/hilar disease activity but without metabolic activity in the lung parenchyma were analyzed, all without treatment.Vital capacity (VC), forced expiratory volume (FEV1) and diffusion capacity of the lung for carbon monoxide (DLCO) were analyzed per group at baseline, i.e. at the time 18F-FDG PET was performed, and after one year follow-up. Results: At follow-up, a significant decrease in DLCO was found in untreated patients with diffuse parenchymal activity.No change in VC or FEV1 could be observed. Treated patients with parenchymal activity showed a significant increase in VC, FEV1 and DLCO, while patients without parenchymal activity did not show any change in PFT. Conclusions: In sarcoidosis, diffuse parenchymal disease imaged by 18F-FDG PET, predicts a future deterioration of DLCO when untreated. Treatment however, improves VC, FEV1 and DLCO significantly suggesting that 18F-FDG PET represents the pulmonary improvement that can be achieved.The absence of metabolic activity in the lung parenchyma justifies a wait-and-see policy.